Fungi Occurrence in Ready-to-Eat Hazelnuts (Corylus avellana) From Different Boreal Hemisphere Areas - Lombardi, Silvia Jane; Pannella, Gianfranco; Tremonte, Patrizio; Mercurio, Ida; Vergalito, Franca; Caturano, Costantino; Maiuro, Lucia; Iorizzo, Massimo; Succi, Mariantonietta; Sorrentino, Elena; Coppola, Raffaele (Frontiers in Microbiology, 2022)
The present study evaluated the fungal contamination of ready-to-eat dried hazelnuts considering for the first time the application of the same condition drying process of several hazelnut cultivars from different boreal hemisphere areas. Fifty lots of hazelnuts (Corylus avellana), belonging to eight cultivars from seven regions in four countries, were analyzed for fungal microbiota, describing both load levels and species diversity. For this purpose, a polyphasic approach consisting of morphological examination (optical and scanning electron microscope observation) and molecular characterization [PCR-DGGE analysis and sequence analyses of the internal transcribed spacer (ITS)] was performed. The results show that different fungal populations occur in dried hazelnuts regardless of their geographical area of production. Although some varieties appear to be relatively less susceptible, species related to Aspergillus, such as A. commune and A. ochraceus, Penicillium, including P. commune, P. solitum, and P. expansum, and Rhizopus, for instance, R. stolonifer and R. oryzae, have generally been found. A related character “hazelnut cultivar—fungi” was found for species related to the genera Trichoderma and Fusarium, including F. oxyxporum, F. solani, and F. falciforme. All 14 species found are known to host pathogenic strains. Therefore, their presence in a ready-to-eat product, such as dried hazelnuts, can pose a real danger to the consumer. Based on these considerations, the development of new protective strategies seems highly desirable. The species-level description of the contaminating fungal community acquired through this study is the starting point for the development of tailor-made protective biotechnologies.